http://i.imgur.com/bjFZw.jpg

That's a picture of the problem.

Where's I'm stuck is why
(1.00 - x)(2.00 - x) = (2x)^2/49.7 = 0.0805x^2

turns into

0.920x^2 - 3.00x + 2.00 = 0

What steps are the book skipping that I'm not following?

Thankyou.

2. (1.00 - x)(2.00 - x) = (2x)^2/49.7 = 0.0805x^2
$\displaystyle 2 - 2x-x + x^2 = 2^2x^2/49.7$
$\displaystyle 2 - 3x + x^2 - 0.0805x^2 = 0.$
Now simplify.

3. Did you just FOIL that or am I an idiot?

4. Originally Posted by climbo
Did you just FOIL that or am I an idiot?
Yes. It is just FOIL.

5. Not to beat a dead horse, but how do you simplify that?

$\displaystyle 2 - 3x + x^2 - 0.0805x^2 = 0.$

The steps confuse me to the point of no return. Don't judge me, I'm extremely rusty and very appreciative of your help.

6. combine like terms then reorder
you should get the given answer

7. Originally Posted by climbo
Not to beat a dead horse, but how do you simplify that?

$\displaystyle 2 - 3x + x^2 - 0.0805x^2 = 0.$

The steps confuse me to the point of no return. Don't judge me, I'm extremely rusty and very appreciative of your help.
Can't you subtract x^2 - 0.0805x^2?